Menjadi Gereja Kaum Miskin Suatu Refleksi Teologi dan Dialog Antara Gereja dan Kaum Miskin dalam Konteks Kemiskinan di Indonesia - Dismas Kwirinus; Heribertus Peri (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2023)
The focus of this research examines the Church of the Poor. The topic of study is related to encounters and dialogue between churches and poor communities in the context of poverty in Indonesia. In the midst of a poverty situation like that which occurs in Indonesia, the church is invited to fulfill its calling. In situations like this, it is clear that the church cannot simply be a donor or Santa organization. This means that to realize its call to the poor, the church must have the courage to become a